Spin-state transition in LaCoO3: direct neutron spectroscopic evidence of excited magnetic states - Podlesnyak, Andrey; Haverkort, Maurits W. (Arxiv, 2005)
A gradual spin-state transition occurs in LaCoO3 around T~80-120 K, whose detailed nature remains controversial. We studied this transition by means of inelastic neutron scattering (INS), and found that with increasing temperature an excitation at ~0.6 meV appears, whose intensity increases with temperature, following the bulk magnetization. Within a model including crystal field interaction and spin-orbit coupling we interpret this excitation as originating from a transition between thermally excited states located about 120 K above the ground state. We further discuss the nature of the magnetic excited state in terms of intermediate-spin (IS, S=1) vs. high-spin (HS, S=2) states. Since the g-factor obtained from the field dependence of the INS is g~3, the second interpretation looks more plausible.
Die Ziffer "3" im Titel ist tiefgestellt
Gesehen am 28.11.2017